Pemanfaatan Sistem Informasi Manajemen dalam Pengambilan Keputusan Strategi di Era Transformasi Digital - Salwa Salsabila; Muhammad Irwan Padli Nasution (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Management Information Systems (MIS) play an important role in supporting strategic decision-making in the era of digital transformation. Through technologies such as Big Data, Artificial Intelligence (AI), and Cloud Computing, MIS is able to provide fast and accurate information that helps managers formulate more effective policies. This study employs a descriptive qualitative approach through a literature review to analyze the utilization of MIS and the challenges encountered in its implementation. The findings indicate that MIS can enhance operational efficiency, strengthen organizational coordination, and enable data-driven decision-making. However, MIS implementation is still hindered by limited digital competency, resistance to change, and data security issues. Therefore, managerial support, improved digital literacy, and effective information governance are essential to optimize the role of MIS in responding to digital- era dynamics.